2020
DOI: 10.1111/sode.12482
|View full text |Cite
|
Sign up to set email alerts
|

Peer victimization and sympathy development in childhood: The moderating role of emotion regulation

Abstract: Although peer victimization is widely considered to be detrimental to children's well-being, knowing what it feels like to be harmed is also thought to contribute to children's sense of concern for others. However, research has yet to establish a clear link between peer victimization and sympathy during childhood. Across two samples of Canadian 4-and 8-year-olds (total N = 504), we examined whether children's emotion regulation capacities (ER) moderated the victimization-sympathy link. Study 1 (n = 300; 33% Eu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Intergroup peer exclusion encompasses verbal or physical aggression, bullying, isolation, denial of access, and information, humiliation, and shaming in social networks [ 6 ]. Generally, it is seen as an inability to form or maintain social relationships [ 7 ], and experiences vary in severity from single to chronic exclusion events [ 8 , 9 ]. Whether the exclusion is acute or chronic in nature, children who are excluded, as well as the perpetrators and witnesses of the exclusion, may suffer extreme distress and isolation, with potentially detrimental effects on their current and future health, behavior, learning ability, and emotions [ 10 , 11 , 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Intergroup peer exclusion encompasses verbal or physical aggression, bullying, isolation, denial of access, and information, humiliation, and shaming in social networks [ 6 ]. Generally, it is seen as an inability to form or maintain social relationships [ 7 ], and experiences vary in severity from single to chronic exclusion events [ 8 , 9 ]. Whether the exclusion is acute or chronic in nature, children who are excluded, as well as the perpetrators and witnesses of the exclusion, may suffer extreme distress and isolation, with potentially detrimental effects on their current and future health, behavior, learning ability, and emotions [ 10 , 11 , 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding individual characteristics, early differences in empathic temperament are at least partly explained by genetic inheritance—by age 3, 47% of the variability in empathy is explained by heritability (Knafo et al, 2008), and among adults heritability estimates range from 27% to 28% for cognitive empathy, and 54% for empathic concern (Melchers et al, 2016; Warrier et al, 2018). In addition, individual differences in social and emotional learning skills, including emotional awareness and self‐regulation skills, have been shown to protect children from victimization (Zych, Farrington, et al, 2019), and may be necessary to enable victims to transform their personal suffering into empathy for others (Jambon et al, 2021; Rieffe & Camodeca, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…With respect to bullying, Farrell and Vaillancourt (2020) found that childhood experiences of peer victimization positively predicted an increasing trajectory of empathic concern during adolescence, but did not predict differences in perspective taking. Another study found that the positive association between victimization and empathic concern for other bullied children, both concurrently and 1 year later, only held for children who reported higher emotion regulation skills (Jambon et al, 2021), suggesting that the ability to manage feelings of personal distress may be critical for transforming negative emotional arousal into an other‐oriented empathic response. Shared experience may contribute to greater feelings of concern by providing the observer with relevant background information from which to organize their empathic response (Batson et al, 2005; Hodges et al, 2010), and orienting the attention of past victims to the current victims' suffering (Preston & de Waal, 2002).…”
Section: Is Peer Victimization Associated With Empathy?mentioning
confidence: 99%
“…Despite documented mean-level developmental and sex differences in ER and empathy/sympathy (Bender et al, 2012;Eisenberg et al, 2006), few studies have tested differential associations between ER and empathy/sympathy across age groups and sex. For the few studies that have been tested, relations between ER and empathy/sympathy were not dependent on these sample characteristics (e.g., Caprara et al, 2010;Jambon et al, 2021;Rivera-Pérez, Leo ´n-Del-Barco, et al, 2020). Nonetheless, given the scarcity of such studies and the theoretical utility of understanding the applicability of our focal effects across different periods of development and for different sexes, we accounted for the moderating effects of age (continuous and categorical) and sex.…”
Section: Sample Characteristicsmentioning
confidence: 99%